Pengaruh Kepemimpinan Diri Sendiri Terhadap Sikap Wirausaha Pada Usaha Makanan Tradisional Di Desa Palung Raya Kecamatan Tambang Kabupaten Kampar - La Ode Syarfan; Andri Kurniawan (UIR Press, 2020)
Lopek Bugi Desa Palung Raya, District Kampar is a home-based traditional food business. In running a business requires self-leadership that requires a willing attitude to accept change. Spread the list of businesses in 2018 as many as 24 businesses with 140 owners and workers. The sampling technique was conducted random sampling of 44 samples by collecting data using questionnaires. The results showed that the Lieliefors L Linearity Test calculated (0.0167) < L tables (0.0974) and sig (p-value) = 200 > 0.05 or Y estimate errors over normal randomized error X or H0 count received. Heteroskedastisity tests observed that residual points were around random horizontal lines (Almost positive and negative inters intervals). Thus, it can be concluded narratively that the assumption of mean error equals 0 is met. Hypothesized testing in linieraitas test Can be concluded that, there is a linear relationship between X and Y because the level of significance of α = 0.05 then H0 is accepted because sig 0.850 > 0.05. Test f states that, It is known that f count= 20,205 and f table= 4.07, meaning f count> f table means significant between variables selfleadership affects Entrepreneurial Attitudes. While in the t test, the correlation between independent selfleadership variables (X) affects entrepreneurial attitudes (Y). This indicates that the higher self-leadership will lead to increased Entrepreneurial Attitudes. Thus this hypothesis states that Self-Leadership has a significant effect on entrepreneurial attitudes in small businesses traditional food